State of the Art in Wind Turbine and Photovoltaic Panels - Bălăceanu, Mihai; Popa, Nicolae-Silviu; Nae, Valentin; Târhoacă, Mircea-Cristache; Popa, Ciprian (Technium Electro, 2024)
This paper functions as an instructional resource for budding researchers in the field of electrical engineering engaged in generating electrical power from renewable energy sources. It will provide insights into wind turbines, listing their constituent parts and fundamental operational principles. Additionally, the paper will delve into the operational principles of photovoltaic panels, their various categories, and their significance within the realm of renewable energy. By perusing this material, readers can develop a comprehensive grasp of these state-of-the-art technologies, ultimately fostering the progress of the field and advocating for a more sustainable future.